1993
DOI: 10.1111/j.1432-1033.1993.tb18107.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of some nuclear nucleases of rat thymocytes and their changes in radiation‐induced apoptosis

Abstract: Three nuclease activites have been found and characterized in rat thymocyte nuclear extracts. A Mn2+-dependent nuclease is loosely bound to nuclear components and can be extracted with 0.35 M NaCI. The enzyme is activated by MnZ+ but not by Mg", Ca2+, or both. Its molecular mass is 36-40 kDa when measured by gel filtration and 37 kDa by SDSPAGE. An acidic nuclease is independent of divalent ions, produces DNA strand breaks with 5'-OH ends, its molecular mass is about 37 kDa. Two fractions of Ca2+Nn2+-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In the final analysis, no overall acceptable degradative scheme has been found, and different cells might use different cleaving activities to disassemble the genome when entering an apop totic cell death pathway. What does appear to be accepted is that only 3' -OH end groups are generated in the laddered DNA in dying cells (Alnemri and Litwack, 1990;Nikonova et at., 1993). This available hydroxyl group permits end-labeling by TdT and has led to wide use and commercialization of the TdT mediated dUTP-biotin nick end labeling (TUNEL) technique (Gavrieli et at., 1992) for in situ identifica tion of DNA fragments in dying cells and tissue sec tions.…”
Section: Discussionmentioning
confidence: 99%
“…In the final analysis, no overall acceptable degradative scheme has been found, and different cells might use different cleaving activities to disassemble the genome when entering an apop totic cell death pathway. What does appear to be accepted is that only 3' -OH end groups are generated in the laddered DNA in dying cells (Alnemri and Litwack, 1990;Nikonova et at., 1993). This available hydroxyl group permits end-labeling by TdT and has led to wide use and commercialization of the TdT mediated dUTP-biotin nick end labeling (TUNEL) technique (Gavrieli et at., 1992) for in situ identifica tion of DNA fragments in dying cells and tissue sec tions.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] In EPC, the DNA fragmentation induced by hypertonic stresses (both 450 and 500 mOsm/kg) as well as by heat shock, UV irradiation, and actinomycin D was partially suppressed by 1 mm Zn2+ ion (Fig. 6).…”
Section: Inhibition Of Dna Fragmentation By Zn2+mentioning
confidence: 99%
“…These results, coupled with the findings with Cd 2+ and Hg 2+ which are classical sulphydryl inhibitors, strongly suggest that a critical thiol is involved in the DNA fragmentation process. The thiol group may be located on the endonuclease itself as Nikonova et al [28] have reported that three nucleases extracted from thymocyte nuclei were inhibited by NEM and idoacetamide. Also, Ribeiro and Carson [29] have described the purification of a CaZ+/Mg 2+ endonuclease from human spleen, which was partially inhibited by NEM.…”
Section: Discussionmentioning
confidence: 99%